Resuscitation fluid practices in Brazilian intensive care units: A secondary analysis of Fluid-TRIPS - de Freitas, Flavio Geraldo Rezende; Hammond, Naomi; Li, Yang; de Azevedo, Luciano Cesar Pontes; Cavalcanti, Alexandre Biasi; Taniguchi, Leandro; Gobatto, André; Japiassú, André Miguel; Bafi, Antonio Tonete; Mazza, Bruno Franco; Noritomi, Danilo Teixeira; Dal-Pizzol, Felipe; et al. (Associação de Medicina Intensiva Brasileira, 2021)
Objective: To describe fluid resuscitation practices in Brazilian intensive care units and to compare them with those of other countries participating in the Fluid-TRIPS. Methods: This was a prospective, international, cross-sectional, observational study in a convenience sample of intensive care units in 27 countries (including Brazil) using the Fluid-TRIPS database compiled in 2014. We described the patterns of fluid resuscitation use in Brazil compared with those in other countries and identified the factors associated with fluid choice. Results: On the study day, 3,214 patients in Brazil and 3,493 patients in other countries were included, of whom 16.1% and 26.8% (p < 0.001) received fluids, respectively. The main indication for fluid resuscitation was impaired perfusion and/or low cardiac output (Brazil: 71.7% versus other countries: 56.4%, p < 0.001). In Brazil, the percentage of patients receiving crystalloid solutions was higher (97.7% versus 76.8%, p < 0.001), and 0.9% sodium chloride was the most commonly used crystalloid (62.5% versus 27.1%, p < 0.001). The multivariable analysis suggested that the albumin levels were associated with the use of both crystalloids and colloids, whereas the type of fluid prescriber was associated with crystalloid use only. Conclusion: Our results suggest that crystalloids are more frequently used than colloids for fluid resuscitation in Brazil, and this discrepancy in frequencies is higher than that in other countries. Sodium chloride (0.9%) was the crystalloid most commonly prescribed. Serum albumin levels and the type of fluid prescriber were the factors associated with the choice of crystalloids or colloids for fluid resuscitation.
Práticas de ressuscitação volêmica em unidades de terapia intensiva brasileiras: Uma análise secundária do estudo Fluid-TRIPS
Keywords: Colloids; Critical care; Crystalloid solutions; Fluid therapy; Hemodynamics; Shock